Correlation of t(14;18) translocation breakpoint site with clinical characteristics in follicular lymphoma - Panjan, Matej (Radiology and oncology (Ljubljana), 2023)
Background: t(14;18)(q32;q21) translocation is an important genetic feature of follicular lymphoma resulting in antiapoptotic B-cell lymphoma 2 (BCL2) protein overexpression. On chromosome 18 breakpoint-site variation is high but does not affect BCL2. Breakpoint most commonly occurs at major breakpoint region (MBR) but may happen at minor cluster region (mcr) and between MBR and mcr at 3'MBR and 5'mcr. The aim of this study was to analyze the correlation of t(14;18)(q32;q21) breakpoint site with clinical characteristics in follicular lymphoma. Patients and methods: We included patients diagnosed with follicular lymphoma who received at least 1 cycle of systemic treatment and had the t(14;18)(q32;q21) translocation detected by polymerase chain reaction (PCR) at MBR, mcr or 3'MBR prior to first treatment. Among patients with different breakpoints, sex, age, disease grade, stage, B-symptoms, follicular lymphoma international prognostic index (FLIPI), presence of bulky disease, progression free survival and overall survival were compared. Results: Of 84 patients, 63 had breakpoint at MBR, 17 at mcr and 4 at 3'MBR. At diagnosis, the MBR group had a significantly lower disease stage than the mcr group. Although not significant, in the MBR group we found a higher progression-free survival (PFS) and overall survival (OS), lower grade, age, FLIPI, and less B-symptoms. Conclusions: Compared to patients with mcr breakpoint, those with MBR breakpoint seem to be characterised by more favourable clinical characteristics. However, a larger study would be required to support our observation.
Keywords: clinical characteristics; folikularni limfom; follicular lymphoma; klinične značilnosti; t(14; 18) translocation; translokacija t(14; 18)